1
$\begingroup$

Okay, I am practicing factoring for an upcoming assignment and I know that this is basic algebra, but I forgot how to attack this polynomial. Every method that I have used so far from simply guessing to using the quadratic formula to long division has failed me in replicating the answer. So either I am attacking this problem wrong up or there is another method that I just forgot.

So here it is: $x^4-2x^2+1=0\\$

The 4 roots of the polynomial are $\pm 1,\pm 1$ (it only has 2 distinct roots).

My confusion is in how to get those values.

Any help in deriving the solution would be greatly appreciated.

$\endgroup$
8
$\begingroup$

Hint:

Set $p=x^2$ to get $$p^2-2p+1=0$$

Solve this and then substitute back $p=x^2$.


Even better would be if you note that $$x^4-2x^2+1=(x^2-1)^2$$

$\endgroup$
  • 1
    $\begingroup$ No need for the quadratic formula, just note that $p^2-2p+1=(p-1)(p-1)=(p-1)^2$. $\endgroup$ – rae306 Oct 25 '14 at 16:28
  • $\begingroup$ I guess, I am just not seeing it. To me $p^2-2p+1=p(p-2)+1=0$ $\endgroup$ – Ryan W. Bentz Oct 25 '14 at 16:31
  • 1
    $\begingroup$ That's true too, but this trinomial can also be factored into $(p-1)(p-1)$. This is called the product sum method. If you don't see this, feel free to use the quadratic formula, which gives the same answers, but is a bit more difficult in this case. $\endgroup$ – rae306 Oct 25 '14 at 16:35
  • $\begingroup$ Right, simple method...$(p-1)(p-1)=0 \implies (p-1)^2=0 \implies (x^2-1)^2=0\\$ Then $(x^2-1)=0 \implies x^2=1 \implies \sqrt{x^2}=\sqrt{1} \implies x=\pm \sqrt{1} = \pm 1$ Then repeat for the other term. Giving 4 roots of $\pm 1$ $\endgroup$ – Ryan W. Bentz Oct 25 '14 at 16:48
  • $\begingroup$ Your method works fine, but I don't understand what you say after the math. $x^4-2x^2+1$ only has 2 roots, which are $x=\pm1$. $\endgroup$ – rae306 Oct 25 '14 at 16:49
2
$\begingroup$

$x^4-2x^2+1=0$ clearly has a root of $1$. Since $\dfrac{x^4-2x^2+1}{x-1}= x^3+x^2-x-1$ you now have $$(x-1)(x^3+x^2-x-1)=0.$$

$x^3+x^2-x-1=0$ clearly has a root of $1$. Since $\dfrac{x^3+x^2-x-1}{x-1}= x^2+2x+1$ you now have $$(x-1)(x-1)(x^2+2x+1)=0.$$

And so on.

$\endgroup$
  • $\begingroup$ So use long division... $\endgroup$ – Ryan W. Bentz Oct 25 '14 at 16:35
  • 1
    $\begingroup$ As someone who struggles to remember the rules for factoring trinomials and greater, it's important to be good at guessing one root and doing long division. $\endgroup$ – Brad Oct 25 '14 at 22:51
2
$\begingroup$

$$x^4-2x^2+1=0\\$$ $$\implies(x^2-1)^2 =0\\$$ $$\implies(x^2-1)(x^2-1)=0\\$$ $$\implies(x+1)(x-1)(x+1)(x-1)=0$$ $$\implies x=\pm1,\pm1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.